EFEKTIVITAS PROGRAM PENINGKATAN PERANAN MENUJU KELUARGA SEHAT SEJAHTERA DI DESA SUKAKARYA KECAMATAN SUKAKARYA KABUPATEN BEKASI - Rachmah Dyah Ayu Mega Fitri; Yeyet Solihat; Evi Priyanti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research was motivated by the problems of the P2WKSS program (Increasing the Role of Women Towards a Healthy and Prosperous Family) which was implemented in Sukakarya Village in 2018, namely there were still assisted women who did not develop their potential, lack of government socialization regarding program objectives and lack of concern for the P2WKSS program after coaching was completed . The purpose of this research is to find out how effective the P2WKSS program has been implemented in Sukakarya Village, Sukakarya District, Bekasi Regency. This research is a qualitative research with descriptive methods. Data collected through observation, interviews, triangulation and documentation. The results of this study indicate that the P2WKSS program has not been effective because of several factors, including the unwillingness of the assisted women and they think it is not important to develop this program, which is more focused on improving infrastructure, there is still the husband's participation in the process of developing assistance, and the unclear use of sewing machine assistance. only kept by the village government after the guidance is complete.